2006
DOI: 10.1177/001789690606500206
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the attitudes, triggers and consequences of hazardous drinking in university students

Abstract: Objective The aim of this paper was to investigate drinking patterns, attitudes towards drinking and predictors of binge drinking as well as negative consequences of binge drinking in students.Design & Method Data was collected by questionnaire from 261 students living on campus at one Welsh university.Results The results showed that levels of drinking were higher than previous studies have revealed. The major triggers to binge drinking were social, and conformity motives were important predictors of hazardous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…180 law students/-Dental:83 %, Law: 71 % Mean age: Dental students – 21.4 years, Law students – 20.4 years Men and women Alcohol use categorised to sensible c 30 % of dental students and 40 % of Law students reported exceeding sensible levels of alcohol consumption c /week Boland et al, 2006 [ 27 ] 2002 A researcher distributed the surveys to students in class, outlined the aims and objectives of the research and collected the completed surveys before departing. Medical students All undergraduate years of medicine 537/63 % 19–22 Men and women CAGE 2002 – 52.5 % of medical students reported a positive CAGE score Faulkner et al, 2006 [ 21 ] - Students living in halls of residence in a campus university in South Wales were eligible for inclusion. Questionnaires were distributed to as many halls as could be accessed and collected two days later.…”
Section: Methodsmentioning
confidence: 99%
“…180 law students/-Dental:83 %, Law: 71 % Mean age: Dental students – 21.4 years, Law students – 20.4 years Men and women Alcohol use categorised to sensible c 30 % of dental students and 40 % of Law students reported exceeding sensible levels of alcohol consumption c /week Boland et al, 2006 [ 27 ] 2002 A researcher distributed the surveys to students in class, outlined the aims and objectives of the research and collected the completed surveys before departing. Medical students All undergraduate years of medicine 537/63 % 19–22 Men and women CAGE 2002 – 52.5 % of medical students reported a positive CAGE score Faulkner et al, 2006 [ 21 ] - Students living in halls of residence in a campus university in South Wales were eligible for inclusion. Questionnaires were distributed to as many halls as could be accessed and collected two days later.…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol abuse is a major risk factor for suicide among individuals between the ages of 10-19 and 20-24 (14). Another study found that all students in the sample consumed a mean of 9.6 drinks per week-over 30% of males consumed more than 21 drinks per week and almost 20% of females consumed more than 14 drinks per week (16). When surveyed, many young adults between the ages of 10-24 already possessed patterns of alcohol use before entering college.…”
Section: Alcohol Use Among College Studentsmentioning
confidence: 99%
“…Statistically, research suggests that roughly 10% of men and about 4% of women in the United States develop alcohol dependence (14). Of the drinkers, 28% said that they, were heavy drinkers and 72% were moderate drinkers, consuming about 11 drinks per week (16). The literature suggests that on average, male students consume seven alcoholic drinks per week and female students consume three per week (15).…”
Section: Alcohol Use Among College Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Undergraduates have been shown to be motivated to drink by social factors (e.g. Faulkner et al 2006;Wicki et al 2010); therefore, undergraduate alcohol consumption behaviour may not be associated with individual differences in impulsivity, but a decision facilitated by conformity to a social norm.…”
Section: Introductionmentioning
confidence: 99%